Damage advancement behavior in braided composite structures for mini aerial vehicles. Issue 11 (18th August 2018) - Zhong, Yucheng; Suraj, Ravindrababu; Wang, Chen; Chia, Elvin Ser Ming; Joshi, Sunil Chandrakant; Chen, Zhong
ABSTRACT: This work provides a systematic approach to accurately predict damage progression in a composite structure subjected to bending load. Landing gear structures for unmanned aerial vehicles were fabricated from braided textile preforms and assessed for flexural behavior. A multiscale finite element analysis model was developed for analyzing the progressive damage of these structures under bending loads. Microscale and mesoscale analyses were carried out first. Subsequently, the results of microscale and mesoscale analyses were used as inputs in macroscale analyses that predicted the progressive damages in the entire landing gear structure. The numerical results were validated by experimental studies.